"A Search for Presence or a Reflection on Absence?": Aesthetics and Ethics in Kate Grenville's One Life: My Mother's Story. (2nd January 2022) - O'Byrne, Cheryl
Abstract: This essay contributes to conversations about the ethical complexities that arise when a writer transforms a subject's firsthand accounts into a narrative for a broad readership. It asks if the aesthetic features of Kate Grenville's One Life: My Mother's Story (2015) can both prioritize readers' engagement and allow for an ethical portrayal of the mother-subject.